Induction of Tertiary Lymphoid Structures With Antitumor Function by a Lymph Node-Derived Stromal Cell Line - Zhu, Genyuan; Nemoto, Satoshi; Mailloux, Adam W.; Perez-Villarroel, Patricio; Nakagawa, Ryosuke; Falahat, Rana; Berglund, Anders E.; Mulé, James J. (Frontiers in Immunology, 2018)
Tertiary lymphoid structures (TLSs) associate with better prognosis in certain cancer types, but their underlying formation and immunological benefit remain to be determined. We established a mouse model of TLSs to study their contribution to anti-tumor immunity. Because the stroma in lymph nodes (sLN) participates in architectural support, lymphogenesis and lymphocyte recruitment, we hypothesized that TLSs can be created by sLN. We selected a sLN line with fibroblast morphology that expressed sLN surface markers and lymphoid chemokines. The subcutaneous injection of the sLN line successfully induced TLSs that attracted infiltration of host immune cell subsets. Injection of MC38 tumor lysate-pulsed dendritic cells activated TLS-residing lymphocytes to demonstrate specific cytotoxicity. The presence of TLSs suppressed MC38 tumor growth in vivo by improving anti-tumor activity of tumor infiltrating lymphocytes with downregulated immune checkpoint proteins (PD-1 and Tim-3). Future engineering of sLN lines may allow for further enhancements of TLS functions and immune cell compositions.